2022
DOI: 10.1503/cmaj.212054
|View full text |Cite
|
Sign up to set email alerts
|

Suicidality among sexual minority and transgender adolescents: a nationally representative population-based study of youth in Canada

Abstract: Background: Very little research has described risk of suicidal ideation and suicide attempt among transgender youth using high-quality, nationally representative data. We aimed to assess risk of suicidality among transgender and sexual minority adolescents in Canada. Methods: We analyzed a subsample of adolescents aged 15–17 years from the 2019 Canadian Health Survey on Children and Youth, a nationally representative, cross-sectional survey. We defined participants’ tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 42 publications
3
12
0
Order By: Relevance
“…Of the participants, 72.3% had seriously thought about taking their own life, 42.7% had attempted suicide, and 57.6% had depressive symptoms. The high rates found in this Brazilian sample are in line with those found in other countries, such as the United States [ 6 , 7 , 40 , 41 ], China [ 8 ], Canada [ 9 ], the United Kingdom [ 7 ], Australia [ 7 ], Japan [ 7 ], and New Zealand [ 5 ]. However, in China [ 8 ], in a binary sample, trans women had significantly higher rates of mental illness than trans men, and our study found no significant difference between genders.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Of the participants, 72.3% had seriously thought about taking their own life, 42.7% had attempted suicide, and 57.6% had depressive symptoms. The high rates found in this Brazilian sample are in line with those found in other countries, such as the United States [ 6 , 7 , 40 , 41 ], China [ 8 ], Canada [ 9 ], the United Kingdom [ 7 ], Australia [ 7 ], Japan [ 7 ], and New Zealand [ 5 ]. However, in China [ 8 ], in a binary sample, trans women had significantly higher rates of mental illness than trans men, and our study found no significant difference between genders.…”
Section: Discussionsupporting
confidence: 88%
“…In China [ 8 ], a survey of young transgender persons found a prevalence of 56.4% for a history of suicidal ideation and 16.1% reported a history of suicide attempts. In Canada [ 9 ], a nationally representative population-based study with young people found that transgender adolescents were at an increased risk of suicidality when compared to their cisgender peers, with 5 times the risk of suicidal ideation and 7.6 times the risk of ever having attempted suicide.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with incidence and prevalence of substance use increasing with age [ 5 , 13 , 42 ]. Further, adolescents who were cis-gender girls, transgender or gender diverse, or who endorsed LGBTQ status had higher odds of being in profiles characterized by more severe and frequent emotional and behavioral disorder symptoms (with or without substance use) [ 19 , 20 , 43 ]. However, these associations were stronger for the low substance use/high emotional and behavior disorder symptom profile than for the profile high in both.…”
Section: Discussionmentioning
confidence: 99%
“…Female adolescents may be more likely to report co-occurring concerns [ 7 ], while transgender or gender diverse adolescents experience greater vulnerability to substance use and mental health concerns [ 19 ]. Both transgender and sexual minority adolescents experience significantly higher rates of suicidality [ 20 ]. Further, severe mental illnesses are often defined by the presence of psychotic symptoms, trauma-related disorders, and/or clinical indicators of acute risk including harm to self, harm to others, and need for hospitalization [ 21 ].…”
Section: Introductionmentioning
confidence: 99%